Constituent elements of the nursing consultation in the pre-natal care in the view of the pregnant women - Ivana Rios Rodrigues; Dafne Paiva Rodrigues; Márcia de Assunção Ferreira; Maria Lúcia Duarte Pereira; Eryjosy Marculino Guerreiro Barbosa (Rev Rene)
Objective: to investigate the constituent elements of the nursing consultation in the prenatal care, in the view of the pregnant women. Methods: a qualitative study, undertaken based on semistructured interviews with 95 pregnant women. The samples were chosen by intentional criteria, until theoretical data saturation took place at 25 interviews, which were processed using the ALCESTE software. The participants undertook intercalated prenatal consultations between the nurse and physician. Results: the conduct undertaken in the first prenatal consultation related to arranging tests and the prescription of folic acid and ferrous sulfate, evidencing the importance of attending the consultations. Furthermore, the discourses are based on advice for general care and the filling out of the ‘pregnant woman’s card’. Conclusion: based on the view of the pregnant women who participated, it was possible to identify that the nursing consultation in the prenatal period was based in technical procedures. Emphasis was placed on the providing of information, but it was not possible to identify feedback on this.